The effects of extraversion, social support on the posttraumatic stress disorder and posttraumatic growth of adolescent survivors of the Wenchuan earthquake. - Xuji Jia; Liuhua Ying; Xiao Zhou; Xinchun Wu; Chongde Lin (PLoS ONE, 2015)
The aim of this study was to examine the relationships among extraversion, social support, posttraumatic stress disorder and posttraumatic growth among adolescent survivors of the Wenchuan earthquake.Six hundred thirty-eight participants were selected from the survivors of the 2008 Wenchuan earthquake. Participants completed four main questionnaires, including the Extraversion Subscale, the Social Support Scale, the Child PTSD Symptom Scale, and the Posttraumatic Growth Inventory.A bivariate correlation analysis revealed significant correlations among extraversion, social support, posttraumatic stress disorder and posttraumatic growth. Extraversion had significant indirect effects on posttraumatic stress disorder (β = -.037, p < .01) and posttraumatic growth (β = .077, p < .001) through social support. The results also indicated that extraversion had a significant direct effect on posttraumatic growth and a nonsignificant direct effect on posttraumatic stress disorder.Social support fully mediates the relationship between extraversion and posttraumatic stress disorder and partially mediates the relationship between extraversion and posttraumatic growth. Psychological interventions and care for survivors of the earthquake should include the various functions and sources of social support and how they serve to benefit individuals.